Potential Cost-Effectiveness of Prenatal Distribution of Misoprostol for Prevention of Postpartum Hemorrhage in Uganda - Lubinga, Solomon J.; Atukunda, Esther Cathyln; Ssalongo, George Wasswa; Babigumira, Joseph B. (PLoS ONE, 2016)
Background: In settings where home birth rates are high, prenatal distribution of misoprostol has been advocated as a strategy to increase access to uterotonics during the third stage of labor to prevent postpartum hemorrhage (PPH). Our objective was to project the potential cost-effectiveness of this strategy in Uganda from both governmental (the relevant payer) and modified societal perspectives. Methods and Finding: To compare prenatal misoprostol distribution to status quo (no misoprostol distribution), we developed a decision analytic model that tracked the delivery pathways of a cohort of pregnant women from the prenatal period, labor to delivery without complications or delivery with PPH, and successful treatment or death. Delivery pathway parameters were derived from the Uganda Demographic and Health Survey. Incidence of PPH, treatment efficacy, adverse event and case fatality rates, access to misoprostol, and health resource use and cost data were obtained from published literature and supplemented with expert opinion where necessary. We computed the expected incidence of PPH, mortality, disability adjusted life years (DALYs), costs and incremental cost effectiveness ratios (ICERs). We conducted univariate and probabilistic sensitivity analyses to examine robustness of our results. In the base-case analysis, misoprostol distribution lowered the expected incidence of PPH by 1.0% (95% credibility interval (CrI): 0.55%, 1.95%), mortality by 0.08% (95% CrI: 0.04%, 0.13%) and DALYs by 0.02 (95% CrI: 0.01, 0.03). Mean costs were higher with prenatal misoprostol distribution from governmental by US$3.3 (95% CrI: 2.1, 4.2) and modified societal (by US$1.3; 95% CrI: -1.6, 2.8) perspectives. ICERs were US$191 (95% CrI: 82, 443) per DALY averted from a governmental perspective, and US$73 (95% CI: -86, 256) per DALY averted from a modified societal perspective. Conclusions: Prenatal distribution of misoprostol is potentially cost-effective in Uganda and should be considered for national-level scale up for prevention of PPH.
Keywords: Prenatal distribution; Postpartum hemorrhage; Uganda